PENGARUH PELAKSANAAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN MEMILIH JASA AKOMODASI (Studi Kasus Hotel Benteng Pekanbaru) - Ahmad Saipul Anwar; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Execution of Promotion is networking of target and target, policy and order giving direction to effort marketing of company from time to time, at every level and reference and also its location, especially as response of company in face of environment and circumstance of emulation changing. Needs consument grow because an motif of pursuant to attribute suit fancy and its requirement in using an service activities, pursuant to the mentioned hence the company have to precisely design strategy of marketing to draw enthusiasm from within x'self of consumer is in order to interested to product of service which on the market so that if consumer have had an interest in the product hence there will be decision to buy the product and generate decision of consumer buy.This research is conducted in Hotel of Benteng Pekanbaru which have location in road street of Soekarno Hatta kav 10-12, Pekanbaru. Target of this Research is conducted to know influence of execution of promotion to decision of buy of at Hotel Benteng Pekanbaru.In this research is methodologies used by quantitative and descriptive with program SPSS, where sampel used by that is patient of visitor of Hotel Benteng Pekanbaru and as source of information is HRD, Front of Office and Manager marketing. To determine sampel use formula Slovin, method of sampling by accidental sampling. Technics of data collecting of through interview, observation and kuesioner.From result analyse data covering validity test, reabilitas, and linear regresi modestly, execution of promotion in research of inimeliputi 4 that good component is advertisement, publicity, sales promotion, and the personal sale. Each owning indicator which each other be interconnected and have an effect on positive to decision of buy of service of room;chamber of Hotel of Benteng PekanbaruKeyword: Execution of Promotion and Consument Decision